Indução do estresse do retículo endoplasmático celular pelo Vaccinia virus: modulação da via UPR durante a infecção viral - Thiago Lima Leão (2013)
The unfolded protein response (UPR) is a cellular response to accumulation of unfolded proteins in the lumen of the endoplasmic reticulum (ER), induced by a variety of external and internal stimuli, including accumulation of misfolded proteins. Viruses such as Vaccinia Virus (VACV) induce host cells to produce large quantities of viral proteins, many of which undergo glycosylation and other modifications in the ER. This large protein input can overwhelm the work capacity of the organelle and consequently activate the UPR of which the inositol-requiring enzyme 1 (IRE1)-dependent pathway is the most conserved component. The aim of this work was to evaluate if the excessive production of recombinant proteins directed to ER, generated from the MVA vector, could trigger the UPR signaling pathway and negatively affect the production of these proteins. Recombinant MVA expressing the protein luciferase addressed or not to ER, were generated and MEFs wild-type or PERK-KO were infected. At different hours post infection, total RNA was extracted and RT-PCR-RFLP tests performed to assess the transcription factor XBP-1 splicing pattern. The results suggest that recombinant protein is being produced by viral vectors. Addictionaly, the data suggest that the UPR signaling pathway is modulated by rMVAs. Moreover, MVA wild-type and VACV-WR affected IRE1in the same way, even in the presence of ER stress inducers. We concluded that IRE1 inhibition represents a previously undescribed poxvirus strategy to modulate cellular stress response.